2015
DOI: 10.1016/j.egja.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of tranexamic acid on perioperative bleeding in pediatric patients undergoing tonsillectomy

Abstract: Background: Tonsillectomy is one of the most common surgery in pediatric and bleeding is one of the most serious complications related to tonsillectomy. Tranexamic acid is a plasminogen inhibitor which has been successfully used to control bleeding in a variety of surgeries. Aim: The aim of the present study was to assess the effect of tranexamic acid on bleeding in pediatric patients undergoing elective tonsillectomy. Materials and methods: The present study included 225 patients classified into three groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
12
1
1
Order By: Relevance
“…The initial search for studies that compared antifibrinolytic drugs to placebo in pediatric surgery retrieved 5,021 hits from which 306 articles were fully screened. In total, 50 randomized placebo-controlled trials were included in this systematic review, among which 15 studies rated good, [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] 19 fair, [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] and 16 poor. [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] Detailed rating informati...…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial search for studies that compared antifibrinolytic drugs to placebo in pediatric surgery retrieved 5,021 hits from which 306 articles were fully screened. In total, 50 randomized placebo-controlled trials were included in this systematic review, among which 15 studies rated good, [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] 19 fair, [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] and 16 poor. [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] Detailed rating informati...…”
Section: Literature Searchmentioning
confidence: 99%
“…28,30-36,38-40,45,47 51,53,54,58,59 Transfusion requirements were reported by 14 studies, 30,31,[33][34][35][36]38,40,45,47,51,53,54,59 reoperation was reported by three studies, 34,50,51 and two studies reported rebleeding. 58,60 The size of the study populations ranged from 26 to 225 patients.…”
Section: Noncardiac Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Se han descrito múltiples factores asociados al sangrado intraoperatorio, tales como: tipo de patología amigdalina subyacente (presencia de fibrosis, amigdalitis crónica) [9], la técnica quirúrgica (técnica caliente o fría) [12], uso de AINEs como el ketorolaco [13], presencia de coagulopatías previas [14], uso de antifibrinolíticos como el ácido tranexámico [15], [16], procoagulantes como el subgalato [17] y el uso de antibióticos [9]. Estos factores son controvertidos y han sido puestos en duda por algunos autores.…”
unclassified